Negative effects of psychotherapy: estimating the prevalence in a random national sample - Bernhard Strauss; Romina Gawlytta; Andrea Schleu; Dominique Frenzl (BJPsych Open, 2021)
Background Negative or adverse effects of psychological treatments are increasingly a focus of psychotherapy research. Yet, we still know little about the prevalence of these effects.